2020
DOI: 10.3390/pathogens9060500
|View full text |Cite
|
Sign up to set email alerts
|

Classical Swine Fever Virus Biology, Clinicopathology, Diagnosis, Vaccines and a Meta-Analysis of Prevalence: A Review from the Indian Perspective

Abstract: Classical swine fever (CSF) is an economically significant, multi-systemic, highly contagious viral disease of swine world over. The disease is notifiable to the World Organization for Animal Health (OIE) due to its enormous consequences on porcine health and the pig industry. In India, the pig population is 9.06 million and contributes around 1.7% of the total livestock population. The pig industry is not well organized and is mostly concentrated in the eastern and northeastern states of the country (~40% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…In order to improve their current control program, the Indian Veterinary Research Institute have incorporated a new safe, live attenuated CSFV vaccine using local strain. This vaccine has been claimed as the best choice for use in the CSF Control Program in the country [ 218 ]. Notoriously, like the findings reported in China, studies based on molecular epidemiology revealed the presence of the CSF genome in cattle serum samples.…”
Section: Emergence Of New Csfv Subgenotype In Endemic Regions Undementioning
confidence: 99%
“…In order to improve their current control program, the Indian Veterinary Research Institute have incorporated a new safe, live attenuated CSFV vaccine using local strain. This vaccine has been claimed as the best choice for use in the CSF Control Program in the country [ 218 ]. Notoriously, like the findings reported in China, studies based on molecular epidemiology revealed the presence of the CSF genome in cattle serum samples.…”
Section: Emergence Of New Csfv Subgenotype In Endemic Regions Undementioning
confidence: 99%
“…The complete genome sequences obtained from NGS can provide detailed genetic information for construction of reliable phylogenetic relationships of CSFVs for monitoring the evolution and transmission patterns during field outbreaks or epidemics of CSF. One phylogenetic analysis using 58 CSFV complete genome sequences from different Asian countries indicated that the circulating Indian CSFV strains belong to different branches of the 1.1 sub-genotype [ 52 ]. These data combined those obtained from other different diagnostic tests can be used for meta-analysis of CSF prevalence, which is important for the investigation of CSF prevalence in different regions [ 52 ].…”
Section: Antigen Detectionmentioning
confidence: 99%
“…One phylogenetic analysis using 58 CSFV complete genome sequences from different Asian countries indicated that the circulating Indian CSFV strains belong to different branches of the 1.1 sub-genotype [ 52 ]. These data combined those obtained from other different diagnostic tests can be used for meta-analysis of CSF prevalence, which is important for the investigation of CSF prevalence in different regions [ 52 ].…”
Section: Antigen Detectionmentioning
confidence: 99%
“…Besides, unavailability of CSF vaccines in sufficient doses to control CSF is another major drawback because of which the disease is frequently reported in endemic foci throughout the country [ 26 ]. Currently, in India, both lapinized and cell-culture adapted lapinized CSF vaccines (Weybridge strain, UK), based on genotype-1.1 are being used to control the disease [ 24 ].…”
mentioning
confidence: 99%